Description of three new species of the genus Herichthys (Perciformes: Cichlidae) from eastern Mexico, with redescription of H. labridens, H. steindachneri, and H. pantostictus - Maza-Benignos, Mauricio De La; Lozano-Vilano, Ma. De Lourdes (Zootaxa, 2013)
Three new species of the genus Herichthys are described on the basis of chromatic, morphometric, and meristic characters. Herichthys pratinus sp. nov. from the Rio Salto in San Luis Potosi is characterized by a steep and shallow predorsal profile, a concavity before the eye, and adult males with a prominent forehead forming a nuchal hump, DXV–XVI, 10–11; and AV, 8–9. Herichthys pame sp. nov. from the Rio Tamasopo in San Luis Potosi is characterized by a gradual and acute predorsal contour, lack of concavity before the eye, and mouth angled slightly downward. Herichthys. molango sp. nov. from Laguna Azteca, Hidalgo is distinguished by small eyes and a slender (slightly broader than long), well-spaced, and indented lower pharyngeal plate with 2 rows of 8–9 medium-sized, lightly pigmented molars flanking the midline. We also provide redescriptions for three species of Herichthys, H. pantostictus, H. labridens, and H. steindachneri and a review of H. bartoni.